Response to Critics: Phenomenalism, Fallibilism and Finitude. Issue 5 (20th October 2022) - Seiberth, Luz Christopher
ABSTRACT: I respond to objections from three rigorous readers challenging me to detail in what sense Sellars is a transcendental philosopher, as well as to defend the claim that 'picturing' is crucial to his account of intentionality. This further involves defending the tenability of transcendental phenomenalism and arguing against scepticism about picturing. Finally, this involves the question of whether the results of transcendental analyses undermine the legitimacy of the Manifest Image, and, consequently, to say what knowledge about phenomena can mean in the succession of conceptual frameworks.